Network Pharmacology and Experimental Verification to Explore the Potential Mechanism of Yin-Huo-Tang for Lung Adenocarcinoma Recurrence - Liu D; Lin S; Li Y; Zhou T; Hu K; Li Q (Dove Medical Press, 2022)
Dianna Liu,1 Shicheng Lin,2 Yuan Li,2 Tian Zhou,1 Kaiwen Hu,1 Quanwang Li1 1Oncology Department, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, 100071, People's Republic of China; 2Graduate School, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of ChinaCorrespondence: Kaiwen Hu; Quanwang Li, Email kaiwenh@163.com; quanwangli@126.comPurpose: Yin-Huo-Tang (YHT) is a classic traditional Chinese prescription, used to prevent lung adenocarcinoma (LUAD) relapse by "nourishing yin and clearing heat". In this study, the mechanism of YHT in LUAD recurrence was investigated.Methods: Firstly, the bioactive compounds and targets of YHT, as well as related targets of LUAD recurrence, were collected from public databases. The protein-protein interaction network, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed to find the pivotal compounds, hub genes, functional annotation and main pathways. Subsequently, RNA sequencing of recurrent tumor tissues from Lewis lung carcinoma mice treated with YHT was used to explore the main pathways. At the same time, pathways screened by network pharmacology and RNA sequencing analysis were considered the most important pathways. Finally, liquid chromatography mass spectrometry was used to validate the pivotal active ingredients. Molecular docking technology was performed to validate the binding association between the hub genes and the pivotal active ingredients. PCR and WB analysis were used to validate the main pathways.Results: There were 128 active compounds and 419 targets interacting with YHT and LUAD recurrence. Network analysis identified 4 pivotal compounds, 28 hub genes and 30 main pathways. Sphingolipid signaling pathway was the common main pathway in network pharmacology and RNA sequencing results. The hub gene related to the sphingolipid signaling pathway was S1PR5. Qualitative phytochemical analysis confirmed the presence of 3 pivotal compounds, namely stigmasterol, nootkatone and ergotamine. The molecular docking verified that the pivotal compounds could good affinity with S1PR5. The PCR and WB analysis verified YHT suppressed Lewis lung cancer cells proliferation and migration by inhibiting the sphingolipid signaling pathway.Conclusion: The potential mechanism and therapeutic effect of YHT against the recurrence of LUAD may be ascribed to inhibition of the sphingolipid signaling pathway.Graphical Abstract: Keywords: sphingolipid signaling pathway, traditional Chinese medicine, S1PR5, stigmasterol, nootkatone, ergotamine